ANALISIS STRATEGI HUKUM REGIONAL ASEAN TERHADAP PENCUCIAN UANG OLEH KORPORASI DALAM KONTEKS NORMA INTERNASIONAL DAN REGULASI NASIONAL - Muhamad Ipan Susila; Ani Purwati; Yuherman (Jurnal Riset Multidisiplin Edukasi, 2025)
This research analyzes the effectiveness of ASEAN regional legal strategies in combating corporate money laundering through the perspective of international norms harmonization and national regulatory implementation. Using normative juridical methods with descriptive-comparative approach, the study examines anti-money laundering legal frameworks in ASEAN region during 2000-2025 period. Findings indicate that despite significant progress in FATF standards adoption and regional cooperation mechanisms strengthening through MLAT 2004, practical implementation still faces regulatory fragmentation challenges and institutional capacity disparities among member states. Digital transformation has created new complexities in corporate money laundering modus operandi, particularly through financial technology and cryptocurrency requiring AML regional framework adaptation. Regulatory arbitrage and forum shopping become major challenges exploited by multinational corporations to avoid detection. The research recommends developing artificial intelligence-based integrated monitoring systems, harmonizing cross-border enforcement procedures, and strengthening capacity building through continuous standardization programs to enhance corporate money laundering eradication effectiveness in ASEAN region.